2019
DOI: 10.1051/e3sconf/201912301007
|View full text |Cite
|
Sign up to set email alerts
|

Selective mining of complex stuctured ore deposits by open stope systems

Abstract: The article studies stability of intervening pillars at underground selective mining of complex structured ore bodies of Kryvyi Rih iron ore basin applying open stope systems that will enable the increased useful mineral component content in the mined ore mass. When calculating an exposure span, the current methods of determining room system constructive elements do not consider dirt thickness. So, it is essential to develop methods of determining room system constructive elements for mining complex structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…As a result of research [1,20], it has been revealed that the shape of the compensation space greatly influences on the rock massif stability in the conditions of the rock pressure manifestation. Thus, it has been proved that when mining the deposit of the main strike using a sloping compensation chamber, the normal stresses in the upper part of outcropping span decrease by 4 times.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of research [1,20], it has been revealed that the shape of the compensation space greatly influences on the rock massif stability in the conditions of the rock pressure manifestation. Thus, it has been proved that when mining the deposit of the main strike using a sloping compensation chamber, the normal stresses in the upper part of outcropping span decrease by 4 times.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a promising method is chemical strengthening or undercutting by a shearer-loader of the seam roof rocks (instead of bottom rocks) with the extraction of the false roof, followed by a more stable roofimmediate. However, it is possible to fundamentally reduce the waste rocks proportion in the rock mass by using new options for selective mining technology with backfilling of the mined-out area [50], [51]. This will make it possible to extract coal with an ash content sufficient for the technological requirements of TPPs.…”
Section: Assessing the Volumes Of Waste Rock Flows Movement And Identifying The Sources Of Their Formationmentioning
confidence: 99%
“…These ore bodies are mined applying surface and underground methods. Underground methods are used to mine rich iron ores with iron content of 57-65% applying stoping systems and bulk caving of ore and overlying rock in proportion of 55% to 45% [5][6][7][8]. Most of underground mines prefer stoping with pillar caving.…”
Section: Introductionmentioning
confidence: 99%